Síndrome de Bayés, accidente cerebrovascular y demencia - Iomini, Pablo (2021)
Bayés’s síndrome is a clinical entity based on the association between advanced interatrial block and the development of supraventricular tachyarrhythmia, being atrial fibrillation (AF), most frequent. This association was discovered by Prof. Antoni Bayés de Luna in the’80s. Further studies by other groups found a strong relationship between Bayés’s syndrome and thromboembolic phenomena, being stroke the most serious. Moreover, patients with this syndrome has an increased incidence of cognitive impairment and dementia. This observation triggered the question about whether the use of an anticoagulation therapy prior to the documentation of AF could prevent A-IAB associated thromboembolic events. There are ongoing studies in different phases of development aiming to compare the efficacy of anticoagulation in patients with A-IAB with no prior documentation of AF. The outcomes of these studies will allow determining the efficacy of this early therapeutic intervention, and help deciding the role of anticoagulation in patients with A-IAB and no demonstrated AF.